Association of changes in lipid levels with changes in vitamin D levels in a real-world setting - Yonghong Li (Nature Portfolio, 2021)
Abstract In clinical trials, vitamin D supplementation has been reported to reduce serum levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) but not high-density lipoprotein cholesterol (HDL-C). In this cohort study we evaluated the association between changes in vitamin D (25-hydroxyvitamin D) and changes in lipid levels in a real-world setting. Changes in lipid levels over a 1-year period were evaluated among individuals whose vitamin D levels increased (group 1) or decreased (group 2) by ≥ 10 ng/mL in year 2018 versus 2017 (cohort 1; n = 5580), in 2019 versus 2018 (cohort 2, n = 6057), or in 2020 versus 2019 (cohort 3, n = 7249). In each cohort, levels of TC, LDL-C, and TG decreased in group 1 and increased in group 2. Between-group differences in average changes in the 3 cohorts ranged from 10.71 to 12.02 mg/dL for TC, from 7.42 to 8.95 mg/dL for LDL-C, and from 21.59 to 28.09 mg/dL for TG. These differences were significant after adjusting for age, sex, race, education, body mass index, blood pressure, smoking status, geographical location, and baseline levels of vitamin D and lipids (P < 0.001). Changes in vitamin D levels were not significantly associated with changes in HDL-C levels.